Development of Virtual Laboratory Chemistry Based on Guided Inquiry on Buffer Solution Material for Senior High School - Muhammad, Fajar Aulia; Suwardi, Suwardi (Journal of Educational Sciences, 2025)
A buffer solution contains many concepts that are both microscopic and macroscopic, as well as symbolic, so a practical approach is needed to make it easier to understand. This study aims to develop a guided inquiry-based chemistry virtual laboratory learning media on buffer solution material. This research uses the 4D development model, including define, design, develop, and disseminate. The instrument used is a product quality assessment sheet, including validation sheets for material experts, media, and practitioners, as well as student responses. The results of the guided inquiry-based chemistry virtual laboratory assessment on buffer solution material by material experts, media, practitioners, and student responses successively obtained an idealized percentage of 98%, 98%, 89%, and 88% in the very good category. Based on the results of the assessment, it can be concluded that the virtual laboratory chemistry learning media based on guided inquiry on buffer solution material developed is feasible to use as an alternative learning media for buffer solution material for grade XI high school students.